A method for preparing an anionic sieving graphene oxide membrane and uses thereof

CN119186281BActive Publication Date: 2026-10-23SHAOXING RES INST OF ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411232988.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2026-10-23
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

然而,在实际应用中已经被证实,氧化石墨烯二维通道膜的阴离子筛分性能并不如预期

Benefits of technology

[0016]上述一种阴离子筛分氧化石墨烯膜的制备方法,通过物理水热还原的方法移除氧化石墨烯纳米片表面的部分含氧官能团,并进一步以带丰富电荷的聚苯乙烯磺酸修饰纳米片,可合理调整纳米片堆叠成膜时二维通道的尺寸,同时增强通道内部的负电性。采用本发明制备得到的氧化石墨烯膜不仅具有稳定且尺寸合理的二维层间通道,而且具有高密度的负电荷。其中,合理的二维通道尺寸有利于单价阴离子的传输,而带高密度负电荷能有效通过尺寸筛分和静电排斥效应阻止多价阴离子的通过。所获得的二维通道堆叠膜具有优异的离子筛分性能,在离子选择性传输、水净化等领域有着良好的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186281B_ABST
    Figure CN119186281B_ABST
Patent Text Reader

Abstract

The application relates to a preparation method and application of an anion sieving graphene oxide film, and belongs to the technical field of new materials. A physical hydrothermal reduction method is used to remove part of oxygen-containing functional groups on nanosheets to obtain a reduced graphene oxide nanosheet dispersion liquid; the reduced graphene oxide nanosheet dispersion liquid is uniformly mixed with a polystyrene sulfonic acid aqueous solution to obtain polystyrene sulfonic acid modified reduced graphene oxide nanosheets; the modified reduced graphene oxide nanosheets are uniformly deposited onto a porous substrate through a vacuum-assisted filtration method to obtain an anion sieving graphene oxide film. The graphene oxide film prepared by the method has stable structure, enhanced negative charges in two-dimensional channels, can efficiently sieve monovalent and divalent anions, and can be applied to the fields of water treatment and energy conversion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new materials technology, specifically a method for preparing anionic sieved graphene oxide membrane and its application. Background Technology

[0002] Ion sieving technology has wide applications in water purification systems, ion batteries, microfluidic systems, element extraction, reverse electrodialysis, energy conversion, and biosensing. Among these, anion sieving plays an irreplaceable role in various fields; a typical example is the separation of chloride and sulfate salts in the chlor-alkali process. - SO4 2- The separation of ions facilitates resource recovery and the acquisition of clean freshwater resources. Membrane separation technology, due to its advantages such as low energy consumption, high efficiency, and environmental friendliness, has become an effective method for achieving ion sieving. In particular, with the development of nanotechnology in recent years, membrane materials have made revolutionary progress, including two-dimensional nanomaterials, carbon nanotubes, nanofibers, metal-organic frameworks, and covalent organic frameworks.

[0003] Among two-dimensional membrane materials, graphene oxide membranes have shown great potential in the field of ion sieving due to their flexible and tunable interlayer space and rich surface chemical properties. Furthermore, the abundant negatively charged oxygen-containing functional groups on the surface of graphene oxide nanosheets can sieve anions through differences in electrostatic repulsion. However, in practical applications, it has been proven that the anion sieving performance of graphene oxide two-dimensional channel membranes is not as expected. There are two possible reasons: first, the hanging energy groups on the surface of graphene oxide nanosheets are hydrophilic, tending to attract water molecules, leading to the expansion of the two-dimensional nanochannels and an increase in interlayer spacing; second, the low-density negative charge in the graphene oxide nanochannels is insufficient to generate a sufficiently strong electrostatic repulsion force with anions.

[0004] Therefore, it is necessary to develop a simple and effective method to precisely customize two-dimensional nanochannels with appropriate size and high negative charge density to achieve efficient sieving of anions. Summary of the Invention

[0005] To address the aforementioned problems in the existing technology, the present invention aims to design and provide a technical solution for the preparation and application of anion-sieving graphene oxide membranes. The method involves partially removing oxygen-containing functional groups from the surface of graphene oxide nanosheets using a simple and green hydrothermal reduction method, and further modifying the nanosheets with polystyrene sulfonic acid molecular chains carrying negatively charged groups. Anion-sieving graphene oxide membranes with excellent separation performance are then prepared by stacking using a vacuum-assisted filtration method.

[0006] The method for preparing anion-sieving graphene oxide membrane is characterized by comprising the following steps: 1) A suspension of graphene oxide nanosheets with a concentration of 0.002-0.5 mg / ml was poured into a reaction vessel and heated to 90℃-180℃ for 1-4 hours to obtain a reduced graphene oxide nanosheet suspension in which some oxygen-containing functional groups on the nanosheet surface were removed. The reduction temperature and time determine the degree of reduction of the nanosheets. When the reduction is too high, the dispersibility of the nanosheets in the aqueous solution will decrease. In addition, if the reduction temperature is too high, it will also destroy the structure of the nanosheets. 2) Mix the suspension obtained in step 1) with a polystyrene sulfonic acid aqueous solution. The concentration of the polystyrene sulfonic acid aqueous solution is 0.05-8.0 mg / ml, and the mass ratio of polystyrene sulfonic acid to graphene oxide nanosheets is 40-1:1 to obtain a polystyrene sulfonic acid modified reduced graphene oxide nanosheet suspension. If the concentration of polystyrene sulfonic acid is too low, it will not be conducive to sufficient contact with the nanosheets. If it is too high, too many molecular chains will adhere to the surface of the nanosheets, affecting the dispersion of the nanosheets. 3) The suspension obtained in step 2) is uniformly deposited onto a porous substrate by vacuum-assisted filtration to form a membrane layer. After drying, an anion-sieving graphene oxide membrane is obtained.

[0007] The method for preparing anionic sieved graphene oxide membrane is characterized in that, in step 1), the graphene oxide suspension is prepared by a modified Hummers method, and its concentration is 0.02-0.2 mg / ml, preferably 0.1-0.15 mg / ml.

[0008] The method for preparing anionic sieved graphene oxide membrane is characterized in that, in step 1), the graphene oxide nanosheets are monolayer structures with a thickness of ~1 nm and an average lateral dimension of ~5 μm.

[0009] The method for preparing anionic sieved graphene oxide membrane is characterized in that, in step 1), the heating temperature is 100℃-150℃, preferably 110℃-120℃, and the heating time is 2-3h.

[0010] The method for preparing anionic sieved graphene oxide membrane is characterized in that, in step 2), the concentration of the polystyrene sulfonic acid aqueous solution is 0.1-5 mg / ml, preferably 2-3 mg / ml.

[0011] The method for preparing anionic sieved graphene oxide membrane is characterized in that, in step 2), the mass ratio of polystyrene sulfonic acid to graphene oxide is 40-1:1, preferably 20-5:1.

[0012] The method for preparing an anion-sieved graphene oxide membrane is characterized in that, in step 3), the average pore size of the porous substrate is 50-500 nm, preferably 100-200 nm.

[0013] The method for preparing anionic sieve graphene oxide membrane is characterized in that, in step 3), the pressure in the vacuum-assisted filtration method is 0.05-0.6 MPa, preferably 0.1-0.2 MPa.

[0014] The method for preparing anionic sieved graphene oxide membrane is characterized in that, in step 3), the drying temperature is 40-70℃ and the drying time is 6-36h; preferably, the drying temperature is 60-65℃ and the drying time is 12-20h. An appropriate drying temperature can remove moisture from the membrane, making the nanosheets stack more tightly. However, if the temperature is too high, the nanosheets will be further reduced, affecting the interlayer spacing.

[0015] The anion-sieving graphene oxide membrane prepared by the method is used in the fields of ion selective transport and water purification.

[0016] The above-described method for preparing anion-sieving graphene oxide membrane involves removing some oxygen-containing functional groups from the surface of graphene oxide nanosheets through physical hydrothermal reduction, and further modifying the nanosheets with highly charged polystyrene sulfonic acid. This allows for the reasonable adjustment of the size of the two-dimensional channels when the nanosheets are stacked into a film, while simultaneously enhancing the negative charge within the channels. The graphene oxide membrane prepared using this invention not only possesses stable and reasonably sized two-dimensional interlayer channels but also exhibits a high density of negative charges. The reasonable two-dimensional channel size facilitates the transport of monovalent anions, while the high density of negative charges effectively prevents the passage of polyvalent anions through size sieving and electrostatic repulsion. The resulting two-dimensional channel stacked membrane exhibits excellent ion sieving performance and shows promising application prospects in ion selective transport, water purification, and other fields. In existing technologies for ion sieving, the impact of a single factor, such as the interlayer spacing or charge distribution within the graphene oxide two-dimensional channels, on ion sieving performance is often only considered. This invention proposes to fully utilize the synergistic effect between these two factors—the combined effect of size sieving and charge repulsion—to achieve highly efficient ion sieving. Furthermore, the technical solution of this invention is simple and environmentally friendly. Using only a controllable physical hydrothermal reduction method and a simple blending method (π-π stacking of two-dimensional nanosheets and polystyrene sulfonate molecular chains), the microscopic control of the interlayer spacing and internal charge of the graphene oxide films can be simultaneously achieved, thereby significantly improving the anion sieving effect. Attached Figure Description

[0017] Figure 1 AFM comparison images of the original graphene oxide nanosheets, the reduced graphene oxide nanosheets, and the reduced graphene oxide nanosheets modified with polystyrene sulfonic acid molecular chains in Example 1 of this invention. Figure 2Schematic diagrams of the mechanisms and microstructures of different membranes in the ion sieving process; Figure 3 The graph shows the sieving performance of graphene oxide nanosheets and polystyrene sulfonic acid for anions at different mass ratios. Detailed Implementation

[0018] The present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] In this invention, graphene oxide nanosheets are prepared using a modified Hummers method. The graphene oxide sheets in the suspension are single-atom-layer thick, with a longitudinal dimension of ~1 nm and a lateral dimension of ~5 μm. The modified Hummers method is a conventional method for preparing graphene oxide nanosheets.

[0020] Example 1 1) The graphene oxide nanosheet suspension prepared by the modified Hummers method was diluted to 0.2 mg / ml. 25 ml of the diluted suspension was poured into a 50 ml reaction vessel and heated in an oven at 120°C for 3 hours. After cooling, the reduced graphene oxide nanosheet suspension was obtained. The AFM characterization results of the nanosheets are as follows: Figure 1 As shown in the figure. The characterization results show that the thickness of the reduced graphene oxide nanosheets is slightly reduced to about 0.9 nm compared to the original graphene oxide nanosheets, indicating that some oxygen-containing functional groups on the surface of the nanosheets have been removed; 2) The suspension obtained in step 1) (25 ml, 0.2 mg / ml) was mixed with a 4 mg / ml aqueous solution of polystyrene sulfonic acid at a volume ratio of 1:1, i.e., the mass ratio of polystyrene sulfonic acid to graphene oxide nanosheets was 1:20. The mixture was stirred thoroughly at room temperature for 2 hours to obtain a suspension of polystyrene sulfonic acid-modified reduced graphene oxide nanosheets. The polystyrene molecular chain contains benzene rings, which can combine with the benzene rings on the reduced graphene oxide nanosheets through π-π interactions. The AFM image of the further modified nanosheets is shown below. Figure 1 The characterization results show that the thickness of the nanosheets has increased to approximately 1.2 nm, indicating that polystyrene sulfonate molecular chains are adsorbed on the surface of the nanosheets. 3) Take 4 ml of the suspension obtained in step 2) and dilute it to 50 ml with deionized water. Use vacuum-assisted filtration to deposit the nanosheets onto a porous cellulose substrate. Then transfer the separation layer with the substrate to an oven at 60°C and dry it for 12 h to obtain an anion sieve membrane.

[0021] The prepared membrane was tested using anion sieving experiments. Under the condition that the feed concentration was 0.1 mol / L, Cl... - The permeation rate is 0.91 mol m -2 h -1 Cl - SO4 2- The selectivity is 80.8%.

[0022] Example 2 The specific steps are the same as in Example 1, except that in step 2), 25 ml of 0.2 mg / ml suspension is mixed with an equal volume of 0.2 mg / ml polystyrene sulfonic acid aqueous solution, that is, the mass ratio of polystyrene sulfonic acid to graphene oxide nanosheets is 1:1.

[0023] Furthermore, the prepared membrane was subjected to anion exchange sieving experiments. Under the condition that the feed concentration was 0.1 mol / L, Cl... - The permeation rate is 1.14 mol m -2 h -1 Cl - SO4 2- The selectivity is 2.9, such as Figure 3 Therefore, it can be seen that when the mass of polystyrene sulfonic acid and reduced graphene oxide nanosheets is relatively low, Cl... - SO4 2- The selectivity is also low. This indicates that a low negative charge within the channel is not conducive to Cl. - SO4 2- Selective screening.

[0024] Example 3 The specific steps are the same as in Example 1, except that in step 2), 25 ml of 0.2 mg / ml suspension is mixed with an equal volume of 1.0 mg / ml polystyrene sulfonic acid aqueous solution, that is, the mass ratio of polystyrene sulfonic acid to graphene oxide nanosheets is 5:1.

[0025] Furthermore, the prepared membrane was subjected to anion exchange sieving experiments. Under the condition that the feed concentration was 0.1 mol / L, Cl... - The permeation rate is 1.06 mol m -2 h -1 Cl - SO4 2- The selectivity is 6.7, such as Figure 3 This indicates that the film prepared at this ratio still lacks sufficient electronegativity, leading to Cl... - SO4 2- The options remain limited.

[0026] Example 4 The specific steps are the same as in Example 1, except that in step 2), 25 ml of 0.2 mg / ml suspension is mixed with an equal volume of 8.0 mg / ml polystyrene sulfonic acid aqueous solution, that is, the mass ratio of polystyrene sulfonic acid to graphene oxide nanosheets is 20:1.

[0027] Furthermore, the prepared membrane was subjected to anion exchange sieving experiments. Under the condition that the feed concentration was 0.1 mol / L, Cl... - The permeation rate is 0.21 mol m -2 h -1 Cl - SO4 2- The selectivity is 66.0, such as Figure 3 It should be noted that in this embodiment, when the mass ratio of polystyrene sulfonic acid to graphene oxide nanosheets increases to 40:1, Cl - The permeation rate of Cl decreased rapidly. - SO4 2- The selectivity also decreased, indicating that an excessive amount of negative charge in the channel is also detrimental to Cl. - SO4 2- Selective screening.

[0028] Example 5 Step 1) Dilute the graphene oxide nanosheet suspension prepared by the modified Hummers method to 0.2 mg / ml, take 25 ml of the diluted suspension and pour it into a 50 ml reaction vessel, and place it in an oven at 90 °C and heat for 4 h. After cooling, the reduced graphene oxide nanosheet suspension is obtained.

[0029] The remaining steps are the same as in Example 1.

[0030] Furthermore, the prepared membrane was subjected to anion exchange sieving experiments. Under the condition that the feed concentration was 0.1 mol / L, Cl... - The permeation rate is 0.76 mol / m³. -2 h -1 Cl - SO4 2- The selectivity was 8.5. Note that in this embodiment, due to the low reducibility of the nanosheets, the interlayer spacing was not effectively controlled, resulting in Cl... - SO4 2- The selectivity is low.

[0031] Example 6 Step 1) Dilute the graphene oxide nanosheet suspension prepared by the modified Hummers method to 0.2 mg / ml, take 25 ml of the diluted suspension and pour it into a 50 ml reaction vessel, and heat it in an oven at 180 °C for 1 h. After cooling, the reduced graphene oxide nanosheet suspension is obtained.

[0032] The remaining steps are the same as in Example 1.

[0033] Furthermore, the prepared membrane was subjected to anion exchange sieving experiments. Under the condition that the feed concentration was 0.1 mol / L, Cl... - The permeation rate is 0.04 mol m -2 h -1 Cl - SO4 2- The selectivity is 12.6. In this embodiment, due to the high reducibility of the nanosheets, the interlayer spacing is drastically reduced, Cl - and SO4 2- The transmission of Cl is simultaneously restricted, making Cl - SO4 2- The selectivity is low.

[0034] As can be seen from Examples 5 and 6, controlling the reduction degree of nanosheets is also an important aspect of this invention.

[0035] Comparative Example 1 Take the same volume and concentration of the original graphene oxide nanosheet suspension as in Example 1 (i.e., 4 ml 0.1 mg / ml), dilute it to 50 ml with deionized water, and further deposit the nanosheets onto a porous cellulose ester substrate using vacuum filtration. Transfer the separated layer with the substrate to an oven at 60°C and dry for 12 h to obtain the original graphene oxide film.

[0036] Furthermore, the prepared membrane was tested using anion sieving experiments. Under the condition that the feed concentration was 0.1 mol / L, Cl... - The permeation rate is 1.09 mol / m³. -2 h -1 Cl - SO4 2- The selectivity is 1.4. It can be seen that although the original graphene oxide film Cl... - The permeation rate is high, but for Cl... - SO4 2- There is almost no selectivity. This is because the interlayer spacing of the original graphene oxide film was not precisely controlled, and its negative charge is relatively weak.

[0037] Comparative Example 2 Step 1) Dilute the graphene oxide nanosheet suspension prepared by the modified Hummers method to 1.0 mg / ml, take 25 ml of the diluted suspension and pour it into a 50 ml reaction vessel, and heat it in an oven at 120 ℃ for 3 h. After cooling, the reduced graphene oxide nanosheet suspension is obtained.

[0038] It can be observed that the reduced graphene oxide nanosheet suspension prepared by the physical hydrothermal method at this concentration exhibited severe aggregation and could not form a film. Therefore, the control and selection of the concentration of graphene oxide before reduction is also an important aspect of this invention.

[0039] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. An anion exchange sieving graphene oxide membrane, characterized in that... Prepared using the following method: 1) Pour a suspension of monolayer graphene oxide nanosheets with a concentration of 0.1-0.15 mg / ml into a reaction vessel and heat at 110℃-120℃ for 2-3 hours to obtain a reduced graphene oxide nanosheet suspension; 2) Mix the suspension obtained in step 1) with a polystyrene sulfonic acid aqueous solution with a concentration of 2-3 mg / ml. The mass ratio of polystyrene sulfonic acid to graphene oxide nanosheets is 1:20 to obtain a polystyrene sulfonic acid modified reduced graphene oxide nanosheet suspension. 3) The suspension obtained in step 2) is deposited onto a porous cellulose substrate with an average pore size of 100-200 nm by vacuum-assisted filtration, and dried in an oven at 60℃-65℃ for 12-20 h to obtain anionic sieved graphene oxide membrane.

2. The anion exchange sieving graphene oxide membrane as described in claim 1, characterized in that... In step 1): the thickness of the graphene oxide nanosheet is ~1 nm and the average lateral dimension is ~5 μm.

3. The anion exchange sieving graphene oxide membrane as described in claim 1, characterized in that... In step 3): the pressure in the vacuum-assisted filtration method is 0.05-0.6 MPa.

4. The anion exchange sieving graphene oxide membrane as described in claim 1, characterized in that... In step 3): the pressure in the vacuum-assisted filtration method is 0.1-0.2 MPa.

5. The application of the anion-sieving graphene oxide membrane as described in claim 1 in the fields of ion selective transport and water purification.